Integration experiences of internationally educated diagnostic radiographers working in the UK. - Elaine Wilkinson; Edozie Iweka; Beverley Snaith; David Omiyi (PLoS ONE)
Background The current diagnostic radiography workforce issues in the UK have led to active recruitment strategies to employ radiographers from overseas. Research into the experience of nurses and other healthcare professions migrating to the UK to work in the NHS report challenges to that transition, however there is a paucity in the research into the experiences of internationally trained diagnostic radiographers. Method This study aimed to explore the experiences of internationally educated diagnostic radiographers (IEDR) working in the UK and their intentions to remain. A UK-wide electronic survey was distributed through research and professional networks and social media in October 2023. Eligibility criteria were diagnostic radiographers, internationally educated, and currently working in the UK. 226 responses were received. Findings There were positive responses related to the workplace support received (positive correlation r > .60 with statistical significance p < 0.05). However, 57.7% did not know what to expect when transitioning to work, and 56.0% experienced differences in societal culture that affected their adaptation to life and work in the UK. 30.2% had experienced workplace bullying and 34.2% felt they did not fit in culturally with the team. Family support, good workplace relationships and appropriate work mentoring were the top factors respondents identified as supporting integration into the UK. Over 40% intended to leave the UK or were uncertain if they would stay. Conclusion The findings indicate that cultural and societal acclimatisation is challenging, and the enormity of relocating to another country requires holistic support for individuals. More can be done to prepare and support the transition of internationally trained diagnostic radiographers into UK life and practice and improve retention.